Analisis Latihan Bowling Olahraga Cricket Pada Atlit Pemula U-17 DKI Jakarta - Mastri Juniarto; Albert Wolter Tangkudung (Riyadhoh : Jurnal Pendidikan Olahraga, 2022)
This study aims to determine the results of bowling cricket training for U-17 athletes in DKI Jakarta. This research was conducted at the Faculty of Sports Science, State University of Jakarta as a training ground for cricket athletes for U-17 athletes in DKI Jakarta. The research method used is descriptive quantitative research method and the technique used is survey. This study aims to determine the level of success and failure of the throwing skills of the DKI Jakarta U-17 cricket athlete team. The technique of this research is a survey, calculated from each throwing ability carried out in the form of a percentage of success. The trick is to calculate the success and failure of the ability to throw. The population in this study were all novice athletes who participated in the DKI Jakarta Cricket training, totaling 27 athletes. The data from the athletes' bowling test revealed that at the initial training stage of less than 6 months the training was still slow, namely the category of lacking in bowling techniques, while at the 2-year training stage it had entered the strong/good category.